029_ - A.B. Sarsenova; M.Zh. Tazhigaliyeva; L.Zh. Shadanova (Academic Journal of Physical and Chemical Sciences, 2019)
Family is a social phenomenon. The content of the family relationship form the subjective rights and obligations of its subjects. The scope of rights and obligations of family members (as well as the grounds for their occurrence, change and termination) is specified in separate institutions of family law. The article analyzes the problem of the application of legislation in the field of family law, arising from the implementation of maintenance obligations. Currently in the Republic of Kazakhstan, a significant part of civil cases are disputes arising from family relationships. This category also includes cases of collecting alimony, changing the amount of alimony, terminating their recovery, or adding or reducing arrears of alimony. If there is no alimony agreement or agreement between the parents, then the order of payment and the amount determined by the court, taking into account the financial situation of both parents.